2013
DOI: 10.1080/13691058.2013.809607
|View full text |Cite
|
Sign up to set email alerts
|

Being tough, being healthy: local forms of counselling in response to adult death in northwest Tanzania

Abstract: While antiretroviral medicines have reduced AIDS-related deaths in sub-Saharan Africa, many people still lose multiple family members and struggle with the social and economic consequences of those deaths. This paper examines how older Tanzanians frame feelings of loss caused by the untimely death of young adults and how they advise other bereaved about how to manage loss. A local concept oyegumisilize--meaning 'to move on and push grief and worries aside'--is employed in offering bereaved persons advice about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Happy (aged 12), who cared for her mother, commented on the way that the community blamed the family for bringing AIDS with them from town: ‘They say, “Why did you bring us this problem?” […] I say, “Don’t talk like that because I don’t know who brought it.”’ This illustrates how women living with HIV and their children are constructed as ‘vectors’ of the disease (Muyinda et al ., 1997) and are stigmatized due to notions of contamination, blame and shame. This supports de Klerk’s (2011: 110) finding that despite having witnessed the impacts of an advanced HIV epidemic, older men and women in rural Kagera region of Tanzania saw AIDS as a ‘disease of sexuality, something that belongs to “those who go in those ways”.…”
Section: Conceptual Frameworksupporting
confidence: 71%
See 1 more Smart Citation
“…Happy (aged 12), who cared for her mother, commented on the way that the community blamed the family for bringing AIDS with them from town: ‘They say, “Why did you bring us this problem?” […] I say, “Don’t talk like that because I don’t know who brought it.”’ This illustrates how women living with HIV and their children are constructed as ‘vectors’ of the disease (Muyinda et al ., 1997) and are stigmatized due to notions of contamination, blame and shame. This supports de Klerk’s (2011: 110) finding that despite having witnessed the impacts of an advanced HIV epidemic, older men and women in rural Kagera region of Tanzania saw AIDS as a ‘disease of sexuality, something that belongs to “those who go in those ways”.…”
Section: Conceptual Frameworksupporting
confidence: 71%
“…Paternal relatives appeared increasingly unable or unwilling to fulfil these kinship responsibilities, owing to poverty and to the scale of orphanhood in Tanzania and Uganda. This resulted in maternal relatives, particularly grandmothers, playing an important role in supporting widows and orphaned children, as other research in Eastern Africa has found (de Klerk, 2011; Nyambedha et al ., 2003; Oleke et al , 2005). Indeed, evidence from 21 African countries, including those with high and low HIV prevalence, suggests that there has been a shift towards grandparents taking an increased childcare responsibility in recent years, especially where orphan rates are growing rapidly (Beegle et al ., 2010).…”
Section: Conceptual Frameworkmentioning
confidence: 84%
“…This also serves as a reciprocal relationship and the norms associated with the event mean that contributions to affected households within the kin network secured reciprocal assistance from these households in the experience of a death in the contributing household. Elsewhere evidence suggests that failing to provide care has been portrayed very negatively and is also strongly socially sanctioned (de Klerk, 2013;Moyer, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…While several qualitative studies of personal networks have been conducted in SSA, including with older adults (De Klerk, 2011; van Eeuwijk, 2014), quantitative studies appear limited to a small study of older HIV-positive Togolese adults (Moore & Prybutok, 2014). In this article, we use personal network data from 5,059 older adults living in rural Mpumalanga, South Africa to examine the extent to which theories developed in higher-income settings about network changes hold in rural South Africa by analyzing how patterns of social contact and support vary by age and gender in this population.…”
mentioning
confidence: 99%